IMPLEMENTATION OF FEES FOR ACQUISITION OF LAND AND BUILDING PAYABLE IN THE FRAMEWORK OF A NATIONAL PROGRAM TO ACCELERATE INTIAL REGISTRATION IN A SYSTEM OF COMPLETE SYSTEMATIC REGISTRATION - Wahyuni Aslamiyah (Universitas Surakarta, 2022)
This article aims to examine the implementation of the debt tax in the framework of the National Program for Accelerating Land Registration in a complete systematic land registration program. The application of the Land and Building Acquisition Fee for the Complete Systematic Land Registration Program by the Regency/City in accordance with Law Number 28 of 2009 becomes tax payable, which according to the provisions of Article 9 paragraph (1) of Law Number 21 of 1997 contains the time owed the tax on the acquisition of land and or building rights is payable from the date of signing and issuance of the Decree on the Granting of Rights, the community participants of the Complete Systematic Land Registration Program sign a statement which is then written on the second page of the certificate that the certificate owner agrees and is aware of signing the agreement that the certificate issued that will be issued has tax payable and must be paid at the time of the acquisition of rights, in other words when the tax payable Acquisition Duty on Land and Buildings is the time for the taxpayer to pay, the place of the tax payable is in the regency, city or province which includes the location of the tax payable land and or buildings. Keywords: Land and building right acquisition fee, Initial registration, complete systematic land registration.